Genome-wide analysis of AGO, DCL and RDR gene families reveals RNA-directed DNA methylation is involved in fruit abscission in Citrus sinensis - Agustín Sabbione; Lucas Daurelio; Abelardo Vegetti; Manuel Talón; Francisco Tadeo; Marcela Dotto (BMC Plant Biology, 2019)
Abstract Background Small RNAs regulate a wide variety of processes in plants, from organ development to both biotic and abiotic stress response. Being master regulators in genetic networks, their biogenesis and action is a fundamental aspect to characterize in order to understand plant growth and development. Three main gene families are critical components of RNA silencing: DICER-LIKE (DCL), ARGONAUTE (AGO) and RNA-DEPENDENT RNA POLYMERASE (RDR). Even though they have been characterized in other plant species, there is no information about these gene families in Citrus sinensis, one of the most important fruit species from both economical and nutritional reasons. While small RNAs have been implicated in the regulation of multiple aspects of plant growth and development, their role in the abscission process has not been characterized yet. Results Using genome-wide analysis and a phylogenetic approach, we identified a total of 13 AGO, 5 DCL and 7 RDR genes. We characterized their expression patterns in root, leaf, flesh, peel and embryo samples using RNA-seq data. Moreover, we studied their role in fruit abscission through gene expression analysis in fruit rind compared to abscission zone from samples obtained by laser capture microdissection. Interestingly, we determined that the expression of several RNA silencing factors are down-regulated in fruit abscission zone, being particularly represented gene components of the RNA-dependent DNA Methylation pathway, indicating that repression of this process is necessary for fruit abscission to take place in Citrus sinensis. Conclusions The members of these 3 families present characteristic conserved domains and distinct expression patterns. We provide a detailed analysis of the members of these families and improved the annotation of some of these genes based on RNA-seq data. Our data suggests that the RNA-dependent DNA Methylation pathway is involved in the important fruit abscission process in C. sinensis.